Development of High-power Permanent Magnet Direct Drive Passenger Locomotive - Zhiqiang YUAN; Min NIE (机车电传动)
In order to meet the needs of the future railway market and improve the key technologies of locomotives and rolling stock, the high-power permanent magnet direct drive technology was studied, and the prototype design and development were carried out. The development of high-power permanent magnet direct drive passenger locomotive had been completed through in-depth study of key technologies such as permanent magnet direct drive system, converter system adapted to permanent magnet direct drive technology, response to back EMF, response to motor loss of excitation, etc. The high-power permanent magnet direct drive passenger locomotive has the characteristics of high transmission efficiency, low life cycle cost, low maintenance workload and environmental protection.